Exportation of MDR TB to europe from setting with actively transmitted persistent strains in peru - Acosta F. (2019)
We performed a cross-border molecular epidemiology analysis of multidrug-resistant tuberculosis in Peru, Spain, and Italy. This analysis revealed frequent transmission in Peru and exportation of a strain that recreated similar levels of transmission in Europe during 2007-2017. Transnational efforts are needed to control transmission of multidrug- resistant tuberculosis globally. © 2019, Centers for Disease Control and Prevention (CDC). All rights reserved.